Pengaruh Variasi Menu, dan Kualitas Layanan Terhadap Keputusan Pembelian pada Warung Mie Ayam Bakso Family Ciawi - Annisa, Ayang Fizahra; Sembiring, Endah Arihta; Komalasari, Aida; Alfiani, Fina; Achyar, Agil Maulana; Rachmat, Yusuf Andhika (Lembaga Pengembangan Kinerja Dosen, 2025)
Warung Mie Ayam Bakso Family is a well-known culinary spot in Warung Panjang Ciawi, largely due to its prime location, making it a preferred choice for locals. This study aims to examine how menu variety and service quality influence purchasing decisions at this stall. The research employs a quantitative approach, surveying all customers with a sample size of 65 respondents. Data was gathered through a questionnaire focused on menu variety, service quality, and purchasing decisions. Analysis was conducted using multiple regression to explore the relationships among these factors. The findings indicate that menu variety positively and significantly impacts purchasing decisions, suggesting that a diverse menu can attract more visitors and encourage repeat purchases. Additionally, service quality significantly influences purchasing decisions, with key aspects such as speed, accuracy, friendliness, and the comfort provided by the staff affecting consumer choices.